The role of archives in Indigenous language maintenance and resurgence - Booth, Samantha (2020)
For centuries, Indigenous peoples have been advocating for their rights to their land, cultures and languages in the context of (settler) colonial institutions that have repressed and removed these rights and knowledges, as well as the mechanisms for their transmission. This thesis attempts to open up questions regarding what settler-colonial archives and archivists could do to support Indigenous language maintenance, resurgence and use, given the reality that most Indigenous languages in Canada (and globally) are declining in use and number of speakers. Using Inuktut (Inuit languages) as a case study, it will outline the circumstances that have led to both this decline and the role that settler-colonial archives have had in it. By examining Inuktut records held by the settler-colonial institution of Hudson’s Bay Company Archives (HBCA) and their Names and Knowledge Initiative as a case study, this thesis will illustrate both the challenges posed by Indigenous language records held by such institutions, as well as the opportunities for (settler) colonial archives to contribute to Indigenous sovereignty over their linguistic data, knowledge and records. It will also explore the use of Indigenous languages in the delivery of services by archives to further support their use as languages of daily life. October 2020